In-frame Val216-Ser217 deletion of KIT in mild piebaldism causes aberrant secretion and SCF response. Issue 1 (July 2018) - Hattori, Mai; Ishikawa, Osamu; Oikawa, Daisuke; Amano, Hiroo; Yasuda, Masahito; Kaira, Kyoichi; Ishida-Yamamoto, Akemi; Nakano, Hajime; Sawamura, Daisuke; Terawaki, Shin-ichi; Wakamatsu, Kaori; Tokunaga, Fuminori; et al.
Highlights: A novel mutation c.645_650delTGTGTC in the KIT gene was identified in piebaldism. After SCF stimulation, Wt and mutant of KIT formed a heterodimer and bound to SCF. The heterodimer KIT mediates reduced phosphorylation of KIT signaling factors. Without Wt KIT, mutant KIT showed secretion defect and accumulated in the ER. Abstract: Background: Piebaldism is a pigmentary disorder characterized by a white forelock and depigmented patches. Although the loss-of-function mutations in the KIT gene underlie the disease, the intracellular dynamics of the mutant KIT are largely unknown. We herein report a Japanese family with piebaldism in which the affected members showed a mild phenotype. Objective: The objective of this study is to investigate the functions and intracellular dynamics of the mutant KIT protein. Methods: We performed genetic analyses of the KIT gene using peripheral blood cells. We analyzed the intracellular localization of the mutant KIT protein in HEK293T cells transfected with wild-type (Wt) and/or mutant KIT genes. Immunoprecipitation analyses, immunoblotting and immunofluorescence studies were performed using antibodies against KIT and downstream signaling proteins. Glycosidase digestion analysis was performed to clarify the intracellular localization of KIT protein. Results: A genetic analysis revealed a novel heterozygous mutation c.645_650delTGTGTC which results in the in-frame deletion of Val 216 and Ser 217 in the extracellular domain of KIT . Immunoprecipitation analyses confirmed that the wild and mutant KIT formed a heterodimer after treatment with stem cell factor (SCF); however, the phosphorylation of the downstream signaling factors was decreased. In an immunofluorescence study, the mutant KIT accumulated predominantly in the endoplasmic reticulum (ER) and was sparsely expressed on the cell surface. A glycosidase digestion study revealed that the mutant KIT is predominantly localized in the ER. Conclusion: These data reveal an aberrant function and intracellular localization of mutant KIT protein in piebaldism.